Factors associated with the improvement of body image dissatisfaction of female patients with overweight and obesity during cognitive behavioral therapy - Yokoyama, Hiroaki; Nozaki, Takehiro; Nishihara, Tomoe; Sawamoto, Ryoko; Komaki, Gen; Sudo, Nobuyuki (Frontiers in Psychiatry, 2022)
Background: Cognitive behavioral therapy (CBT) has become one of the most commonly used psychotherapeutic treatments for obesity. It stems from CBT for bulimia nervosa and binge eating disorder, which focuses on amelioration of the eating behavior and body image dissatisfaction (BID), but usually does not focus on weight loss. In contrast, CBT for obesity focuses on weight loss, as well as eating behavior and BID. It is at present unclear whether the improvement of BID during CBT for obesity is associated with improvement of factors other than weight loss. Objective: The purpose of this study was to determine whether improvement of BID during CBT for obesity was associated with improvement of factors other than weight loss. Methods: One hundred and sixty-five women (BMI 31.8±5.2kg/m2, age 49.3±10.5 years) with overweight or obesity completed a 7-month CBT-based weight loss intervention. BID, depression, anxiety, binge eating, and perfectionism were assessed at both baseline and the end of the intervention through the use of psychological questionnaires. Results: Percent total weight loss, baseline BID, baseline BED, change in depression (Δdepression), Δstate anxiety, Δtrait anxiety, Δbinge eating, and Δperfectionism were significantly correlated with ΔBID. Multiple regression analysis showed that baseline BID, baseline BED, percent total weight loss, Δbinge eating, and Δdepression were independently associated with ΔBID. Conclusion: Improvement of binge eating, and improvement of depression, as well as weight loss, were independently associated with amelioration of BID.